Pupuk organo-kimia untuk pemupukan bibit kelapa sawit Organo-chemical fertilizer for oil palm seedling fertilization - Laksmita Prima SANTI; Didiek Hadjar GOENADI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2008)
SummaryThe availability of high quality and quantity of oil palm seedling needs consistent support of fertilization programs for economic production. Organo-chemical fertilizer with rock phosphate and urea added was initiated to increased economic value of agriculture and estate crops residues. The prototype of organo-chemical fertilizer has 10% organic C, 11% N, 8% P, 1% K and 4% humic acid respectively. Based on greenhouse experiments, organo-chemical fertilizer treated to oil palm seedlings tends to provide a better vegetative growth of the seedlings. Dry weights of leave, stem, and root of the seedlings applied with 100 g organo-chemical fertilizer plus 10 g KCl to each seedling were significantly different compared to the standard dosage conventional fertilizer. This organo-chemical fertilizer could be applied as conventional fertilizer substitute.Ringkasan Ketersediaan bibit kelapa sawit ber-kualitas dengan kuantitas yang terus meningkat memerlukan dukungan program pemupukan yang konsisten untuk mencapai tingkat produksi yang ekonomis. Pembuatan pupuk organo-kimia dengan penambahan batuan fosfat dan N ditujukan untuk meningkatkan nilai ekonomi limbah pertanian dan perkebunan. Prototipe pupuk organo-kimia ini mengandung 10% C-organik, 11% N, 8% P, 1% K dan 4% asam humik. Pemberian 100 g pupuk organo-kimia yang ditambah 10 g KCl per bibit menghasilkan berat kering daun, batang, dan akar yang lebih baik dan berbeda nyata apabila dibandingkan dengan peng-gunaan pupuk konvensional dosis standar. Berdasarkan hasil tersebut, prototipe pupuk organo-kimia ini dapat digunakan sebagai substitusi pupuk konvensional untuk pemupuk-an bibit kelapa sawit.